Testing consumer theory: evidence from a natural field experiment - Maja Adena; Steffen Huck; Imran Rasul (Journal of the Economic Science Association, 2017)
We present evidence from a natural field experiment designed to shed light on whether individual behavior is consistent with a neoclassical model of utility maximization subject to budget constraints. We do this through the lens of a field experiment on charitable giving. We find that the behavior of at least 80% of individuals, on both the extensive and intensive margins, can be rationalized within a standard neoclassical choice model in which individuals have preferences, defined over own consumption and their contribution towards the charitable good, satisfying the axioms of revealed preference.
Keywords: C93; D01; D12; D64; 330; natural field experiment; revealed preference